The Impact of Digital Marketing And Intellectual Capital On Business Performance (Case Study Of SMEs In Depok City, West Java) - Hadi Wijaya (Best Journal of Administration and Management, 2024)
This study explores the impact of digital marketing and intellectual capital on the business performance of SMEs in Depok City. Using a quantitative approach, this research analyzes data obtained from 100 respondents through online questionnaires. The results of multiple linear regression analysis indicate that both digital marketing and intellectual capital have a significant influence on business performance. Digital marketing, measured through variables such as interactivity, site design, cost/transaction, and incentive programs, has been proven to increase customer engagement and online transaction volumes. On the other hand, intellectual capital, consisting of human capital, structural capital, and relational capital, plays a crucial role in enhancing the operational efficiency and profitability of companies. Business performance measurements in this study include profitability, operational efficiency, and customer satisfaction. The coefficient of determination (R²) value of 77.2% indicates that the digital marketing and intellectual capital variables together explain most of the variability in business performance. These findings are consistent with previous studies showing that the use of digital technology in marketing and the management of intellectual capital can enhance a company's competitiveness and overall performance. Thus, this research makes a significant contribution to the literature on digital marketing and intellectual capital management, offering practical insights for business practitioners to improve their marketing strategies and intangible asset management.